Qualitative and Quantitative Identification of Alcohol using the Conway Microdiffusion Method and Gas Chromatography-Flame Ionization Detector (GC-FID) on Evidence at the East Java Polda Bidlabfor - Lailatul Mubarokah; Meilisa Rusdiana Surya Efendi (Prodi Kimia, 2024)
Driving under the influence of alcohol is a safety issue of increasing public concern. Alcohol is a factor in many categories of accidents. Investigations and resolution of legal problems need to be followed up until the case is resolved in court. Items in the form of physical evidence related to the crime scene, victims and suspects need to be identified. Based on this, one of the topics raised in this research includes the results of identification and analysis of criminal cases involving alcohol consumption which were tested qualitatively and quantitatively, so that evidence can be determined during the investigation process as to whether there is alcohol content in it. In the process of qualitative identification of alcohol content, it is carried out using the Conway Microdiffusion method which states that the urine evidence is positive for alcohol, which is indicated by the color changing to green. Meanwhile, identification of alcohol levels in evidence is carried out using a Gas Chromatography -Flame lonization Detector (GC-FID). Analysis of the alcohol content in the evidence stated that the presence of ethanol was 0.0352%.